Laser etching of austenitic stainless steels for micro-structural evaluation. (June 2015) - Baghra, Chetan; Kumar, Aniruddha; Sathe, D.B.; Bhatt, R.B.; Behere, P.G.; Afzal, Mohd
Abstract: Etching is a key step in metallography to reveal microstructure of polished specimen under an optical microscope. A conventional technique for producing micro-structural contrast is chemical etching. As an alternate, laser etching is investigated since it does not involve use of corrosive reagents and it can be carried out without any physical contact with sample. Laser induced etching technique will be beneficial especially in nuclear industry where materials, being radioactive in nature, are handled inside a glove box. In this paper, experimental results of pulsed Nd-YAG laser based etching of few austenitic stainless steels such as SS 304, SS 316 LN and SS alloy D9 which are chosen as structural material for fabrication of various components of upcoming Prototype Fast Breeder Reactor (PFBR) at Kalpakkam India were reported. Laser etching was done by irradiating samples using nanosecond pulsed Nd-YAG laser beam which was transported into glass paneled glove box using optics. Experiments were carried out to understand effect of laser beam parameters such as wavelength, fluence, pulse repetition rate and number of exposures required for etching of austenitic stainless steel samples. Laser etching of PFBR fuel tube and plug welded joint was also carried to evaluate base metal grain size, depth of fusion at welded joint and heat affected zone in the base metal. Experimental results demonstrated that pulsed Nd-YAG laser etching is a fast and effortless technique which can be effectively employed for non-contact remote etching of austenitic stainless steels for micro-structural evaluation. Highlights: Remote etching of SS 304, SS 316 LN, SS alloy D9 samples was carried out using Nd-YAG laser. Threshold fluence for etching was dependent on energy and wavelength of incident radiation. Grain structure was revealed using Nd-YAG laser beam of wavelength 1064 nm, 532 nm and 355 nm. 1064 nm and 532 nm radiation can be used for etching through laminated glass.